STRESS SOLDIERS IN THE AREA OF SPECIAL RISKS - P. P. Patachov (Кубанский научный медицинский вестник, 2014)
The purpose of the study to determine the stress in 60 military special units. Stress resistance was assessed by changes regulatory and adaptive status at baseline and during the action of stress factor - service in the area of special risk. The study was conducted among first called to military and among military personnel with experience in the areas of particular risk. At high levels of stress index regulatory and adaptive status was more than 100 and stressors was not significantly altered or was slightly higher, while a moderate level was reduced to 88.